2015
DOI: 10.1016/j.jcm.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of American Chiropractic Association Members’ Experiences, Attitudes, and Perceptions of Practice in Integrated Health Care Settings

Abstract: Objective: The purpose of this study is to examine the self-report of experiences, attitudes, and perceived educational needs of American Chiropractic Association members regarding practice in integrated health care settings. Methods: This was a descriptive observational study of the American Chiropractic Association members. Participants completed an electronic survey reporting their current participation and interest in chiropractic integrated practice. Results: The survey was completed in 2011 by 1142 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The investigator-designed instrument included questions similar to those contained in widely used surveys of chiropractic practice, such as the National Board of Chiropractic Examiners' Job Analysis of Chiropractic survey 11 and the American Chiropractic Association's member survey of integrated practice. 6 We also asked participants about their interest in joining a planned, broader qualitative case study of chiropractors working in integrated health care settings. The online survey was pretested for functionality by members of the research team and evaluated for face and content validity by DCs on staff at the chiropractic research center.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The investigator-designed instrument included questions similar to those contained in widely used surveys of chiropractic practice, such as the National Board of Chiropractic Examiners' Job Analysis of Chiropractic survey 11 and the American Chiropractic Association's member survey of integrated practice. 6 We also asked participants about their interest in joining a planned, broader qualitative case study of chiropractors working in integrated health care settings. The online survey was pretested for functionality by members of the research team and evaluated for face and content validity by DCs on staff at the chiropractic research center.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Private sector medical settings, ranging from small primary care clinics to large health care systems in the United States, have introduced chiropractic care. [6][7][8][9][10] A survey by the National Board of Chiropractic Examiners Practice Analysis of Chiropractic reported that 9% of doctors of chiropractic (DCs) practice in settings other than chiropractic offices, including 7.8% who work in an "integrated health care facility," with 3.6% of those surveyed identifying that they hold hospital staff privileges. 11 The health care literature rarely describes characteristics of chiropractic practice in the US private sector; most reports are single-site case studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 According to the report, chiropractors will be integrated and exposed to allopathic physicians with increasing frequency through student clerkships, residencies, and chiropractic government programs, such as the Loan Repayment Program of the National Health Service Corps. 7 There is a growing trend of chiropractors practicing in various private medically integrated settings within the United States. 8 Increased numbers of graduates and established chiropractors are seeking employment in traditional medical settings.…”
Section: Introductionmentioning
confidence: 99%